Anti-oxidative constituents of Musa balbisiana Colla fruit extract and evaluation of hepatoprotective activity in CCl4-induced hepatotoxicity in Swiss albino mice - Nabanita Baruah, Madhubanti Das, Kandarpa Kumar Saikia, Jogen Chandra Kalita (Journal of Applied Pharmaceutical Science, 2024)
Carbon tetrachloride is employed to induce hepatotoxicity in experimental animals to mimic oxidative stress caused by several factors in humans and impair liver functions and lead to hepatic damage. Fruits of Musa balbisiana Colla are rich in bioactive compounds and hold therapeutic and nutritional worth. This current study aims to explore the phytochemical constituents, antioxidant effects, and hepatoprotective activity of a methanolic extract derived from the unripe fruit pulp of M. balbisiana Colla via phytochemical screening, evaluation of antioxidant activity, in vivo experiments in Swiss albino mice through monitoring of the body and the liver weight, estimation of hepatic biomarkers, enzymes, malondialdehyde (MDA), and cytokines along with immunohistochemical and histopathological study. The methanolic fruit extract administration minimized hepatic biomarker and MDA levels along with the cytokines and also elevated superoxide dismutase, catalase, plus glutathione content compared to the hepatotoxic group (p < 0.05). Immunohistochemical findings and histopathological examinations of the liver tissues from methanolic extract-treated mice displayed the down regulation of transforming growth factor beta in hepatic parenchymal tissues and re-establishment of standard structural attributes of hepatic tissue. The outcomes of our research illustrate that the methanolic fruit extract of M. balbisiana Colla administration assists in hepatotoxicity attenuation.
Keywords: Antioxidant, carbon tetrachloride, hepatotoxicity, immunohistochemistry, histopathological